Vórtices em modelos-sigma O(3) acoplados não-minimamente e num background gravitacional - Souza, Pablo Rodrigo Alves de (2006)
We consider in this work the σ O(3) Maxwell-Chern-Simons-Higgs Abelian Model with magnet dipole moment immersed in a gravitational background. We used Bogomol'nyi method for the get autoduals equations of the system. With appropriate choice for the whether complete square in energy functional we verify to be possible obtain autodual equations without ne essity to take in consideration an aid eld. The other side, the right generality of the method possibilitate that it be made, offering autoduals equations with aid field, showing a grate similarity with a equations for the ase of the doble dinamic model (Maxwell and Chern-Simons) an a gravitational background, discussed in literature